Decrements in lung function and respiratory abnormalities associated with exposure to diacetyl and 2,3-pentanedione in coffee production workers - Virji, Mohammed Abbas; Fechter-Leggett, Ethan D.; Groth, Caroline P.; Liang, Xiaoming; Blackley, Brie H.; Stanton, Marcia L.; LeBouf, Ryan F.; Harvey, R. Reid; Bailey, Rachel L.; Cummings, Kristin J.; Cox-Ganser, Jean M. (Frontiers in Public Health, 2022)
Coffee production workers are exposed to complex mixtures of gases, dusts, and vapors, including diacetyl and 2,3-pentanedione which occur naturally during coffee roasting and are also present in flavorings used to flavor coffee. This study evaluated associations of these α-diketones with lung function measures in coffee production workers. Workers completed questionnaires and their lung function was assessed by spirometry and impulse oscillometry (IOS). Personal exposures to diacetyl, 2,3-pentanedione, and their sum (SumDA+PD) were assigned to participants and metrics of highest 95th percentile (P95), cumulative, and average exposure were calculated. Linear and logistic regression models for continuous and binary/polytomous outcomes, respectively, were used to explore exposure-response relationships adjusting for age, body mass index, tenure, height, sex, smoking status, race, and allergic status where appropriate. Decrements in percent predicted forced expiratory volume in 1 second (ppFEV1) and forced vital capacity (ppFVC) were associated with highest-P95 exposures to 2,3-pentanedione and SumDA+PD. Among flavoring workers, larger decrements in ppFEV1 and ppFVC were associated with highest-P95 exposures to diacetyl, 2,3-pentanedione, and SumDA+PD. Abnormal FEV1, FVC, and restrictive spirometric patterns were associated with highest-P95, cumulative, and average exposures for all α-diketone metrics; the associations for the latter two outcomes were observed among flavoring and non-flavoring workers. Small airways abnormalities on IOS had elevated odds for highest-P95 exposure to α-diketones. These results may be affected by small sample size, few cases of abnormal spirometry, and healthy worker effect. Associations between lung function abnormalities and exposure to α-diketones suggests it may be prudent to consider exposure controls.